IMPROVING THE PROCESS OF SPECIFIC STRENGTH AND PHYSICAL FITNESS OF ATHLETES THROUGH EXERCISES IN "ZAJA POWER" SPORTS EQUIPMENT - Kubitdinov, Jamshid (Журнал иностранных языков и лингвистики, 2024)
The main purpose of using special sports equipment "ZAJA POWER" is to improve the capabilities of special physical, elasticity and vestibular apparatuses of athletes during pre-competition training. This equipment makes it possible to expand the possibilities of improving the necessary physical qualities of wrestlers of different weight categories during training.